Enhanced Performance of CAP System Using an Overlap Frequency-Domain Equalization Scheme - Jing He; Huan Dong; Rui Deng; Teng Li; Lin Chen (IEEE Photonics Journal, 2016)
In this paper, an overlap frequency-domain equalization (OFDE) scheme is proposed and experimentally demonstrated in an intensity modulation and direct-detection optical communication system with carrierless amplitude and phase (CAP) modulation. Moreover, the negative chirp property of the Mach-Zehnder modulator (MZM) for a CAP32/64/128 system is also investigated. After 100-km standard single-mode fiber transmission, the experimental results show that at the bit error ratio (BER) of 3.8 × 10-3, the receiver sensitivities can be improved by 0.6 and 0.4 dB for CAP32 and CAP64 systems by utilizing the OFDE method, respectively. In addition, the receiver sensitivity is improved by 0.5 dB for CAP128 system at the bit error ratio (BER) of 2.4 × 10-2. Compared with the FDE based on cyclic prefix (CP), the spectral efficiency of the CAP system with the OFDE scheme can be improved by 12.18%.